Beyond dichotomies and continua?: an interactional approach to the grammar of clause combining in Japanese. (November 2016) - Suzuki, Ryoko; Thompson, Sandra A.
Abstract: The category of 'adverbial clause' seems to be relatively well-justified for understanding the grammar of the everyday spoken languages of Europe, although fuzzy boundaries are generally recognized. In this paper, we explore whether the category 'adverbial clause' is useful for understanding conversational Japanese by considering the behavior of the three most frequent clause connectors, kara 'because/so', kedo 'but', and -tara 'if'. Noting the reliance of this category on a biclausal 'main' vs. 'dependent' distinction, we consider four frequent patterns in our data which challenge the advisability of positing 'adverbial clause' for the grammar of this language: a) the 'main' clause is structurally 'less than' a main clause; b) the 'main clause' is missing; c) the alleged 'adverbial clause' or the alleged 'main clause', or the combination, consists of fixed expressions; d) the clause combination typically consists of more than two clauses. We conclude that the notion of 'adverbial clause' needs to be augmented with accounts of these robust clause combining patterns. Highlights: We question whether the category 'adverbial clause' is useful for understanding the grammar of conversational Japanese. Numerous instances of the three most frequent clause connectors challenge the 'adverbial' and 'main' clausal relationship. Viewing the 'main' and 'adverbial' clausal relationship as a continuum cannot be upheld for Japanese conversation.